2015
DOI: 10.1016/j.juro.2015.02.2941
|View full text |Cite
|
Sign up to set email alerts
|

CD103 + Tumor Infiltrating Lymphocytes Predict a Favorable Prognosis in Urothelial Cell Carcinoma of the Bladder

Abstract: Our findings suggest that CD8(+) T cells might have a significant role in tumor immunity by expressing CD103 in intratumor regions of bladder urothelial cell carcinoma tissues. Intratumor CD103(+) TILs could potentially serve as a prognostic marker in patients with bladder urothelial cell carcinoma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

11
127
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 142 publications
(139 citation statements)
references
References 29 publications
11
127
0
1
Order By: Relevance
“…It was first identified in association with intraepithelial CD8 T cells and has been shown to be upregulated in CD8 T cells after antigen stimulation, but can also be expressed by regulatory FoxP3-positive CD4 T cells and by activated dendritic cells (12). Nevertheless, our studies in ovarian cancer show that the majority of CD103-positive cells are CD8 T cells and similar findings were reported in lung, colorectal, and bladder cancer (13)(14)(15)(16). CD103 expression on CD8 T cells is upregulated in response to simultaneous TGFb1 stimulation and antigen recognition (17).…”
Section: Introductionsupporting
confidence: 86%
“…It was first identified in association with intraepithelial CD8 T cells and has been shown to be upregulated in CD8 T cells after antigen stimulation, but can also be expressed by regulatory FoxP3-positive CD4 T cells and by activated dendritic cells (12). Nevertheless, our studies in ovarian cancer show that the majority of CD103-positive cells are CD8 T cells and similar findings were reported in lung, colorectal, and bladder cancer (13)(14)(15)(16). CD103 expression on CD8 T cells is upregulated in response to simultaneous TGFb1 stimulation and antigen recognition (17).…”
Section: Introductionsupporting
confidence: 86%
“…Along the same lines, an enhanced CD103 + TIL subset correlated with increased intraepithelial lymphocyte infiltration [26, 27], supporting the hypothesis that CD103 promotes recruitment of T RM cells within epithelial tumor islets. The intra-epithelial location of CD103 + CD8 + T cells was also observed in colorectal and bladder cancers, and was associated with expression of E-cadherin on tumor cells [28, 29]. Consistently, studies performed with viable human tumor slices [30] and autologous tumor antigen-specific CTL clones showed that CD103 contributes to T-cell recruitment within epithelial tumor regions and enhances intratumoral T-cell early signaling [31].…”
Section: Introductionmentioning
confidence: 79%
“…These cells are also found in various tumors, including melanoma [78], lung cancer [27, 39], urothelial cell carcinoma [29] and endometrial adenocarcinoma [79]. Tumors with a high density of CD8 + T cells showed enrichment for transcripts linked to tissue-T-cell-residency, such as CD103 [38].…”
Section: Role Of Trm In Immune Surveillance and Immunotherapymentioning
confidence: 99%
See 1 more Smart Citation
“…Reports have demonstrated that a high number of tumour‐infiltrating T RM cells is linked to improved prognosis in patients with urinary bladder, lung, cervical and ovarian cancers [7, 8, 9, 10]. The improved prognosis is due to the capacity of T RM cells to produce IFN‐γ upon in‐situ antigen recognition [11], resulting in the recruitment of circulating T cells from the blood [12].…”
Section: Introductionmentioning
confidence: 99%